Alternative Reagents for Methotrexate as Immobilizing Anchor Moieties in the Optimization of MASPIT: Synthesis and Biological Evaluation. Issue 5 (16th February 2015) - De Clercq, Dries J. H.; Risseeuw, Martijn D. P.; Karalic, Izet; De Smet, Anne‐Sophie; Defever, Dieter; Tavernier, Jan; Lievens, Sam; Van Calenbergh, Serge
Abstract We report the evaluation of two alternative chemical dimerizer approaches aimed at increasing the sensitivity of MASPIT, a three‐hybrid system that enables small‐molecule target protein profiling in intact human cells. To circumvent the potential limitations related to the binding of methotrexate (MTX) to endogenous human dihydrofolate reductase (DHFR), we explored trimethoprim (TMP) as an alternative prokaryote‐specific DHFR ligand. MASPIT evaluation of TMP fusion compounds with tamoxifen, reversine, and simvastatin as model baits, resulted in dose–response curves shifted towards lower EC50 values than those of their MTX congeners. Furthermore, a scalable azido‐TMP reagent was synthesized that displayed a similar improvement in sensitivity, possibly owing to increased membrane permeability relative to the MTX anchor. Applying the SNAP‐tag approach to introduce a covalent bond into the system, on the other hand, produced an inferior readout than in the MTX‐ or TMP‐tag based assay.